1966
DOI: 10.1113/jphysiol.1966.sp007909
|View full text |Cite
|
Sign up to set email alerts
|

The variation in isometric tension with sarcomere length in vertebrate muscle fibres

Abstract: 1. The variation of isometric tetanus tension with sarcomere length in single fibres from frog striated muscle has been re‐investigated with special precautions to ensure uniformity of sarcomere length within the part of the fibre being studied. 2. In most respects the results of Ramsey & Street (1940) were confirmed, but (a) the peak of the curve was found to consist of a plateau between sarcomere lengths of 2·05 and 2·2 μ, (b) the decline of tension above this plateau is steeper than found by Ramsey & Street… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

113
1,798
14
33

Year Published

1980
1980
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 2,761 publications
(2,004 citation statements)
references
References 14 publications
113
1,798
14
33
Order By: Relevance
“…At extremely short muscle lengths, thick filaments (myosin) collide with Z-lines, inhibiting adequate binding with actin (thin filaments) and thus, decreasing tension development. 6 In the SCI group, it seems that this inability to generate torque occurred at even some neutral muscle lengths, which would suggest sarcomere shortening.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…At extremely short muscle lengths, thick filaments (myosin) collide with Z-lines, inhibiting adequate binding with actin (thin filaments) and thus, decreasing tension development. 6 In the SCI group, it seems that this inability to generate torque occurred at even some neutral muscle lengths, which would suggest sarcomere shortening.…”
Section: Discussionmentioning
confidence: 97%
“…This phenomenon, known as the length-tension relationship, is attributed to the degree of overlap between the actin and myosin filaments within the myofibrils. 6 A major limitation in the majority of studies that have examined various muscle property changes after SCI is the assumption that there is no change in the lengthtension relationship. A change in this relationship would not only affect muscle characteristics but would also imply a change in the optimal angle for force generation.…”
Section: Introductionmentioning
confidence: 99%
“…In that case the percentage excess tension would be constant over the whole range of muscle lengths. The increase in percentage excess tension comes into evidence at those muscle lengths where, by reference to the relationship between tension and actin-myosin overlap (Gordon et al, 1966b), cross bridges can be made at the mid-sarcomere terminals of the actin filaments. At shorter lengths this is excluded by the geometry of the system.…”
Section: Discussionmentioning
confidence: 99%
“…Clearly the phenomenon ofexcess tension cannot be explained in terms of actin-myosin overlap as in the sliding filament hypothesis (Gordon et al, 1966a and1966b;Huxley, 1957). Sugi (1972) suggested that, during the process of stretch, some of the cross bridges are so displaced that they are brought into a "lockedon" situation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation